The Effect of Squat Jump and Split Squat Jump Plyometric Training on Leg Power in Soccer Athletes - Aditya Eka Candra; Komarudin; Alen Rismayadi (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine the Effect of Squat Jump and Split Squat Jump Plyometric Exercises on the Leg Power of Football Athletes, with the research design applied in this study was